Relationship between HER-2, COX-2, p53 and clinicopathologic features in gastric adenocarcinoma. Do these biomarkers have any prognostic significance? - Ugraş, Nesrin; Özgün, Gonca; Ocakoğlu, Gökhan; Yerci, Ömer; Öztürk, Ersin (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of this study was to examine the expression of HER-2, p53 and COX-2 in gastric adenocarcinoma and to investigate whether these markers were useful in predicting the clinicopathologic features. Materials and Methods: Primary gastric adenocarcinoma specimens were obtained from 56 patients who underwent total/subtotal gastrectomy with extended lymphadenectomy between December 2011 – December 2012. We investigated the association between the expression of these markers and clinicopathologic factors by immunohistochemistry. Results: COX-2 positive cases were detected in 28 (50%) of the 56 patients and COX-2 expression was significantly correlated with presence of perineural invasion (p=0,032). 37 cases (66.1%) were defined positive for p53. The expression of p53 was significantly correlated with increasing age (p=0,003), but there was no correlation with other clinicopathological variables. Among the 56 primary gastric cancers, 9 (16.1%) cases showed intermediate (2+) positive expression and 7 (12.5%) cases showed (3+) positive expression for HER-2. No significant correlations were determined between HER-2 and the other variables. Conclusion: Although, this study failed to show any relationship between HER-2 and clinicopathological factors, but our results demondtrated that COX-2 expression might serve as a powerful indicator for estimating perineural invasion, which is an independent worse prognostic factor for survival in gastric adenocarcinoma. Additionally, detecting the expression of p53 can assist with the treatment options for elderly patients with gastric adenocarcinoma. A better understanding of HER-2, COX-2 and p53 expression in gastric adenocarcinoma may improve the staging strategies and influence new treatment modalities.